The Effectiveness of Creating Assessment Questions Through Google Form as a Digital Learning Assessment Tool - Anry Ani; Muhammad Dalimunthe; Ernita Daulay (Universitas Islam Negeri Palopo, 2025)
This study explores English teachers’ perceptions of the process of creating assessment questions using Google Form and how this process is perceived to support effective digital learning assessment. Conducted in an Islamic senior high school in Indonesia, this qualitative research involved two English teachers selected for their experience in designing Google Form based assessments. Data were collected through semi-structured interviews and documentation, and analyzed using Miles and Huberman’s (2014) interactive model consisting of data condensation, data display, and conclusion drawing. The findings reveal that teachers followed a structured and reflective workflow consisting of four stages: planning, designing, implementing, and evaluating. In the planning stage, teachers aligned learning objectives, indicators, and assessment purposes before organizing questions in Google Form. During the designing stage, teachers utilized quiz mode, sectioning, automatic scoring, and feedback features to construct assessments that were practical, coherent, and supportive of students’ learning. In the implementation stage, Google Form enabled both classroom-based and online administration, allowing teachers to accommodate students with varying internet access while monitoring submissions in real time. In the evaluation stage, teachers benefited from Google Form’s analytics, including automatic scoring and visualized data summaries, which helped them identify common errors and plan follow-up instruction. Overall, teachers perceived Google Form as an effective digital assessment tool because it enhances efficiency, improves assessment organization, supports feedback provision, and facilitates data-driven instructional decisions. However, the study acknowledges limitations related to the small number of participants and the absence of classroom observations. These findings highlight the importance of integrating digital literacy training and further research to explore broader and more diverse assessment contexts.